2009
DOI: 10.1002/anie.200903462
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Construction of Polycyclic Indoles through Olefin Cross‐Metathesis/Intramolecular Friedel–Crafts Alkylation under Sequential Catalysis

Abstract: The combination of mechanistically distinct organocatalysis and transition-metal catalysis has enabled novel transformations beyond those possible with single catalytic systems.[1] Sequential catalysis involving a binary catalytic system often reduces labor and waste and enables the use of more readily available starting materials for a given transformation.[2] Chiral Brønsted acids have been shown to be efficient catalysts for asymmetric Friedel-Crafts reactions. [3,4] In particular, intramolecular Friedel-Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(44 citation statements)
references
References 64 publications
0
39
0
5
Order By: Relevance
“…In this regard, Bandini and Eichholzer reported an elegant allylic alkylation of indoles in the presence of a gold complex, providing an efficient synthesis of 1‐vinyl‐ and 4‐vinyl‐THCs in a highly enantioselective manner 3f. Furthermore, You and co‐workers described an olefin cross metathesis (CM)/intramolecular asymmetric Friedel–Crafts alkylation sequence, which offered a powerful platform to construct enantioenriched tetrahydropyrano[3,4‐b]indoles (THPIs) and tetrahydro‐β‐carbolines (THBCs) 3g…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Bandini and Eichholzer reported an elegant allylic alkylation of indoles in the presence of a gold complex, providing an efficient synthesis of 1‐vinyl‐ and 4‐vinyl‐THCs in a highly enantioselective manner 3f. Furthermore, You and co‐workers described an olefin cross metathesis (CM)/intramolecular asymmetric Friedel–Crafts alkylation sequence, which offered a powerful platform to construct enantioenriched tetrahydropyrano[3,4‐b]indoles (THPIs) and tetrahydro‐β‐carbolines (THBCs) 3g…”
Section: Methodsmentioning
confidence: 99%
“…However, with Hoveyda-Grubbs 2nd generation catalyst and/or Zhan-1B catalyst in the presence of additives such as trifluoroacetic acid (TFA) or HCl, the RCM proceeded smoothly with high conversion furnishing the desired macrocycle in 68% yield. 100 …”
Section: Synthesis Of Sb1518 (Pacritinib 1)mentioning
confidence: 97%
“…A tandem olefin metathesis/Brønsted acid‐catalyzed transformation strategy was also described by You and co‐workers . In a series of studies, the authors reported enantioselective CM/intramolecular Friedel‐Crafts, RCM/isomerization/Pictet–Spengler, and CM/intramolecular aza‐Michael tandem reactions that enabled straightforward syntheses of polycyclic indole derivatives with excellent yields and ee values (Scheme ).…”
Section: Defining Tandem Catalysismentioning
confidence: 98%